2012
DOI: 10.1111/j.1476-5381.2012.01923.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids and β2‐agonists upregulate mitogen‐activated protein kinase phosphatase 1: in vitro mechanisms

Abstract: BACKGROUND AND PURPOSEAirway remodelling is a consequence of long-term inflammation and MAPKs are key signalling molecules that drive pro-inflammatory pathways. The endogenous MAPK deactivator -MAPK phosphatase 1 (MKP-1) -is a critical negative regulator of the myriad pro-inflammatory pathways activated by MAPKs in the airway. EXPERIMENTAL APPROACHHerein we investigated the molecular mechanisms responsible for the upregulation of MKP-1 in airway smooth muscle (ASM) by the corticosteroid dexamethasone and the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 42 publications
(68 reference statements)
3
44
0
Order By: Relevance
“…Given the relatively low efficacy as a cAMP-inducer in ASM cells, therefore RNO (at 1000 nM) only minimally increased formoterol-induced MKP-1 mRNA expression and protein upregulation and the impact was not significant. Consequently, TNF-induced IL- (12)), as well as steroids (dexamethasone (11,14), fluticasone: (12, 14)). Together cAMP-elevating agents and steroids can act in an additive manner to increase MKP-1 upregulation and we have shown this with steroids and LABA added in combination (11,12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the relatively low efficacy as a cAMP-inducer in ASM cells, therefore RNO (at 1000 nM) only minimally increased formoterol-induced MKP-1 mRNA expression and protein upregulation and the impact was not significant. Consequently, TNF-induced IL- (12)), as well as steroids (dexamethasone (11,14), fluticasone: (12, 14)). Together cAMP-elevating agents and steroids can act in an additive manner to increase MKP-1 upregulation and we have shown this with steroids and LABA added in combination (11,12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies in ASM cells have confirmed that stimuli that increase cAMP induce expression of the cAMP-dependent anti-inflammatory protein MKP-1 (5,(11)(12)(13). Because RNO (at 1000 nM) increased cAMP production in response to formoterol, we hypothesized that RNO will augment MKP-1 expression in response to the long-acting β2-agonist in ASM cells.…”
Section: Effect Of Rno (1000 Nm) On Formoterol-induced Mkp-1 Mrna Expmentioning
confidence: 99%
“…Indeed, the dual-specificity mitogen-activated protein kinase (MAPK) phosphatase, dual-specificity phosphatase 1 (DUSP1), is induced by glucocorticoids to switch off MAPK signaling and thereby reduce inflammatory gene expression (Clark et al, 2008). Since the effect of LABAs and glucocorticoids on DUSP1 expression appears additive Manetsch et al, 2012), this offers some explanation for the effects of combination therapy. Notwithstanding effects on DUSP1 expression, synergistic enhancement of glucocorticoid-dependent transcription by the cAMP/protein kinase A (PKA) pathway is well established (Rangarajan et al, 1992;Nordeen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…MKP-1 is a MAPK deactivator with multiple modes of anti-inflammatory action: it is an endogenous protein that functions as a negative feedback effector to repress MAPK-mediated proinflammatory signaling and cytokine secretion (7,19), and it can be upregulated by anti-asthma medicines such as ␤ 2 -agonists and corticosteroids (8,20,21,27,28), serving as an important way in which these front-line asthma medicines achieve their anti-inflammatory function.…”
mentioning
confidence: 99%